PM-IRRA Spectroelectrochemistry of Hexacyanoferrate Films in Layer-by-Layer Polyelectrolyte Multilayers - Villalba, Matias Ariel (2013)
In situ polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS) under potential control is used to study self-assembled layer-by-layer (LbL) poly(allylamine) (PAH) and poly(acrylic acid) (PAA) multilayers containing the hexacyanoferrate redox system on conductive substrates. Two systems were examined, which differ in the way the redox complex is entrapped in the LbL polyelectrolyte multilayer: In system I, the LbL polyelectrolyte multilayer, self-assembled by alternate immersion in PAH and PAA, was exchanged in a 2 mm K3Fe(CN)6 solution of pH 3.5 for 30 min and then thoroughly rinsed with water. In system II, the 2 mm K3Fe(CN)6 solution was complexed with PAA prior to self-assembly with PAA. PM-IRRAS studies demonstrate the potential dependence of the vibrational modes of the polyelectrolyte backbones and the CN stretching modes, which are sensitive to the redox charge in the iron center.